Magnet-responsive, superhydrophobic fabrics from waterborne, fluoride-free coatings. Issue 2 (3rd January 2018) - Fu, Sida; Zhou, Hua; Wang, Hongxia; Ding, Jie; Liu, Shuai; Zhao, Yan; Niu, Haitao; Rutledge, Gregory C.; Lin, Tong
Abstract : Durable superhydrophobic fabrics with magnetic response ability have been prepared by waterborne, fluoride-free coatings. Abstract : In this study, durable superhydrophobic fabrics with magnet responsive properties were prepared by a two-step coating technique using polydopamine (PDA), Fe3 O4 nanoparticles, and hexadecyltrimethoxysilane as coating materials. The coated fabrics exhibit fast magnetic responsivity and a water contact angle of 156°. The coating is durable enough to withstand at least 50 cycles of home laundering and 500 cycles of Martindale abrasions without losing its superhydrophobicity and magnetic properties. The PDA pre-coating plays a significant role in improving the adhesion of hydrophobic Fe3 O4 nanoparticles on fabric surface. The coated fabric is highly oleophilic (oil contact angle = 0°). When used for absorbing oil, the coated fabric floats naturally on the surface of oily water, and it can be moved to approach oil drops under magnetic actuation. The fabric is reusable for at least 10 cycles. This may offer an environmentally friendly way to prepare "smart" oil-recovery materials.